Analisis studi kelayakan bisnis aspek lingkungan pada Bank Syariah Indonesia KCP Jembrana - Rofika, Haniatur; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
This research aims to determine a business feasibility study in terms of environmental aspects at the financial institution Bank Syariah Indonesia, Jembrana Sub-Branch Office, Bali. This research uses a qualitative research method with a descriptive approach with primary data research type. The analytical tool in this research uses a Likert scale which adds up the scores from all question items. The results of this research show that BSI KCP Jembrana has good environmental criteria.